Developing Creative Competencies in 5th–7th Grade Students through Visual Arts Classes - Vosiyeva Aziza To‘xtaqulovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines effective pedagogical methods for developing artistic creativity and creative thinking competencies in 5th–7th grade students. It analyzes strategies such as individual and group activities, project-based learning, experimentation, and interactive approaches in visual arts classes. The findings suggest that improving pedagogical methods significantly enhances students’ creative thinking, artistic expression, and aesthetic perception.